2019
DOI: 10.3389/fmed.2019.00067
|View full text |Cite
|
Sign up to set email alerts
|

Polyphosphates and Complement Activation

Abstract: To sustain life in environments that are fraught with risks of life-threatening injury, organisms have developed innate protective strategies such that the response to wounds is rapid and localized, with the simultaneous recruitment of molecular, biochemical, and cellular pathways that limit bleeding and eliminate pathogens and damaged host cells, while promoting effective healing. These pathways are both coordinated and tightly regulated, as their over- or under-activation may lead to inadequate healing, dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 81 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…50,51 Only for the long-chain polyP polymers, a modulating effect on blood coagulation and innate immunity has been reported. 7,52 Results on the role of short-chain polyP have been published for the first time only recently. 53 In this report, it has been shown that polyP acts on both macrophage and fibrocyte differentiation.…”
Section: Papermentioning
confidence: 99%
“…50,51 Only for the long-chain polyP polymers, a modulating effect on blood coagulation and innate immunity has been reported. 7,52 Results on the role of short-chain polyP have been published for the first time only recently. 53 In this report, it has been shown that polyP acts on both macrophage and fibrocyte differentiation.…”
Section: Papermentioning
confidence: 99%
“…Complement activation plays an important part in the host response to pathogens. Polyphosphates have been suggested to suppress the complement pathway (7, 29), although this mechanism has not been clearly elucidated. Elevated expression of the complement-derived anaphylatoxin, C5a, and interaction with its receptor, C5aR1, drive the pathophysiology of ALI (16, 17, 19).…”
Section: Resultsmentioning
confidence: 99%
“…As described above, the possible anti-inflammatory effects of polyP, which are thought to be mediated through the suppression of the complement system, are discussed ( 53 , 54 ). However, the conflicting possibility that polyP has the potential to induce thrombosis should be noted.…”
Section: Discussionmentioning
confidence: 99%